An evaluative study to find the correlation between semitendinosus graft dimension with respect to patient’s anthropometry - Tanmay Datta; Dibyendu Biswas; Kunal Mondal; Santu Sarkar (Asian Journal of Medical Sciences, 2022)
Background: A prospective study of a cohort of anterior cruciate ligament (ACL) reconstructed patients 7 years after surgery revealed degenerative radiographic changes in 95% of patients, and only 47% were able to return to their previous activity level following ACL reconstruction. Aims and Objectives: The aims of this study were to find the correlation between Semitendinosus graft dimension with respect to patients anthropometry such as age, height, weight, body mass index (BMI), and true leg length (TLL). Materials and Methods: The proposed study was the patients coming to orthopedics-outpatient department and emergency with 30 complete thickness ACL tears which were screened and recruited based on fulfillment of inclusion and exclusion criteria from January 2020 to August 2021 (20 months duration). The sample size was sufficient to draw conclusive findings. Correlation was calculated by Pearson correlation analysis. The Pearson product-moment correlation coefficient was a measure of the linear dependence between two variables X and Y. P≤0.05 was considered for statistically significant. Results: The age has positive correlation with graft length (r=0.11) and relatively strong positive correlation with graft diameter (r=0.437). Height has relatively strong positive correlation with graft length (r=0.4258) and graft diameter (r=0.1375). Weights have strong positive correlation with graft length (r=0.604). TLL also had positive correlation with graft length (0.23) and graft diameter (r=0.1). Conclusion: In selective cases, graft may be reinforced with additional Hamstring tendon harvest like gracilis or any alternative graft such as Bone–patellar tendon–bone (BPB) and Peroneus longus tendon autograft that may be taken to prevent graft failure and future complications. This current data can be a reference for surgeons in preoperative planning and counseling to patients about alternative autograft selection.